The Importance of Patent-Based Technological Prospects and their Search Objectives - Paranhos, Rita de Cassia Santos (2018)
Currently, the focus of technological prospecting through patents is focused mainly on search for priority and monitoring. There is little information on search strategies for other patent prospecting objectives other than those cited above. Thus, the present work aims to contribute with guidelines for technological prospection based on patents according to the purpose of the search. For this, from a bibliographic research in scientific databases; documental research in the electronic address of the World Intellectual Property Organization and databases of patent offices systematized information on diversified strategies depending on the objectives of the search of data. As results, there were shown the guidelines on patent-based technological prospecting according to the search objective.